Disparities in acute in‐hospital cardiovascular care for Aboriginal and non‐Aboriginal South Australians. Issue 5 (5th September 2016) - Tavella, Rosanna; McBride, Katharine; Keech, Wendy; Kelly, Janet; Rischbieth, Amanda; Zeitz, Christopher; Beltrame, John F; Tideman, Philip A; Brown, Alex
Abstract: Objectives: To assess differences in the rates of angiography and subsequent revascularisation for Aboriginal and non‐Aboriginal South Australians who presented with an acute coronary syndrome (ACS); to explore the reasons for any observed differences. Design: Analysis of administrative data with logistic regression modelling to assess the relationship between Aboriginal status and the decision to undertake diagnostic angiography. A detailed medical record review of Aboriginal admissions was subsequently undertaken. Setting: Emergency ACS admissions to SA cardiac catheterisation hospitals, 2007–2012. Participants: 13 701 admissions of patients with an ACS, including 274 Aboriginal patients (2.1%). Major outcome measures: Rates of coronary angiography and revascularisation; documentation of justification for non‐invasive management. Results: After adjustment for age, comorbidities and remoteness, Aboriginal patients presenting with an ACS were significantly less likely than non‐Aboriginal patients to undergo angiography (odds ratio [OR], 0.4; 95% CI, 0.3–0.5; P < 0.001). There was no significant difference in the rates of revascularisation for Aboriginal and non‐Aboriginal patients who had undergone angiography. Reasons for Aboriginal patients not undergoing angiography included symptoms being deemed non‐cardiac (16%), non‐invasive test performed (8%), and discharge against medical advice (11%); the reasons were unclear for 36% of Aboriginal patients. Conclusions: After controlling for age and other factors, the rate of coronary angiography was lower among Aboriginal patients with an ACS in SA. The reasons for this disparity are complex, including patient‐related factors and their preferences, as well as the appropriateness of the intervention. Improved consideration of the hospital experience of Aboriginal patients must be a priority for reducing health care disparities.